Strengthening Inclusive Islamic Education: Building Islamic Boarding School-Based Foundations - Maula, Nikmatul; Jazilurrahman, Jazilurrahman; Suhermanto, Suhermanto (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
This study aims to describe how to strengthen Islamic boarding school-based inclusive education at the Subulus Salam Islamic boarding school Pajarakan Probolinggo. In order to obtain data from research results, researchers used a qualitative case type approach. This research was conducted at the Subulus Salam Islamic boarding school. Data collection techniques with participant observation, in-depth interviews and documentation. While the data analysis technique uses the Spradley model with four types of analysis, namely domain analysis, taxonomic analysis, component analysis, and theme analysis. The results of this study indicate that the strategies undertaken to strengthen inclusive Islamic education based on Islamic boarding schools at the Subulus Salam Islamic boarding school are inclusive Islamic education policies, development of inclusive Islamic education curricula, integration of inclusive values through learning in schools, internalization of inclusive values through religious activities. and social, Kiai's exemplary role model.